Effecting a University’s Mission: The Praxis of Charism - Murray, OSA, Robert J. (Catholic Education: A Journal of Inquiry and Practice, 2002)
Religious communities engaged in educational ministry have been challenged by the Second Vatican Council both to reappropriate the initial charism of their founders and to review their ministry in the schools staffed by their communities. Compounding this challenge has been the shift in the number of members of the founding congregations in their faculties. This article reframes the discussion in terms of an issue of committed culture. After presenting a theological foundation and sociohistorical critique of charism, a praxis model for mission effectiveness as it is applied to student orientation within a Catholic university setting will be introduced.